SCHIP Expansion and Parental Coverage: An Evaluation of Wisconsin's BadgerCare - Wolfe, Barbara; Kaplan, Thomas; Haveman, Robert; Cho, Yoonyoung (My University, 2005)
In the wake of the expansion of Wisconsin's public health-insurance program, this research explores the extent to which a program like Wisconsin's BadgerCare reduces the proportion of the low-income population without health-care coverage.